BANK INNOVATIONS AND THEIR IMPACT ON THE ECONOMY - Abduraximova Dilora Karimovna (International Journal of Innovations in Engineering Research and Technology, 2023)
In the current century, the penetration of financial technologies in banking has widely changed the architecture of the banking service market of the world. Their appearance affects not only the banking systems of countries but also the economies of countries. The article analyzes the influence of the implementation and use of innovative banking technologies on the financial sector and economies of the different regions and countries of the world.